Structural Modeling of the Relationship Between Mindfulness and Posttraumatic Growth: The Mediating Role of Difficulties in Emotion Regulation and Self-Compassion in Patients with Rheumatoid Arthritis - Naseri, Fatemeh; Hadi Omid , Mohammad Reza (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study aimed to model the structural relationship between mindfulness and posttraumatic growth through the mediating roles of difficulties in emotion regulation and self-compassion in patients with rheumatoid arthritis. Methods and Materials: In terms of purpose, the present study was applied research, and in terms of data collection method, it was a descriptive correlational study using a structural equation modeling approach. The statistical population consisted of all patients with rheumatoid arthritis who attended hospitals and rheumatology clinics in Tehran during the autumn of 2025. A total of 550 patients were selected using purposive sampling and completed the Five Facet Mindfulness Questionnaire developed by Ruth A. Baer and colleagues (2006), the Difficulties in Emotion Regulation Scale by Kimberly L. Gratz and Lizabeth Roemer (2004), the Self-Compassion Scale by Kristin Neff (2003), and the Posttraumatic Growth Inventory by Richard G. Tedeschi and Lawrence G. Calhoun (1996). Data analysis was conducted using Pearson correlation coefficients and structural equation modeling with SPSS version 26 and AMOS version 24 software. Findings: The findings indicated that the proposed model demonstrated a good fit (GFI = 0.995, CFI = 0.987, IFI = 0.987, RMSEA = 0.034, χ²/df = 1.623). All direct and indirect path coefficients in the structural model were significant (P < 0.001). Mindfulness had a positive and significant effect on self-compassion (β = 0.243) and a negative and significant effect on difficulties in emotion regulation (β = -0.263). In addition, difficulties in emotion regulation had a negative and significant effect on posttraumatic growth (β = -0.641), whereas self-compassion had a positive and significant effect on posttraumatic growth (β = 0.607). The indirect effect of mindfulness on posttraumatic growth through difficulties in emotion regulation and self-compassion was 0.316 and statistically significant (P = 0.012). Conclusion: Mindfulness is a significant predictor of posttraumatic growth in patients with rheumatoid arthritis, both directly and indirectly through reducing difficulties in emotion regulation and enhancing self-compassion. Therefore, the design and implementation of psychological interventions based on mindfulness, emotion regulation, and self-compassion may serve as effective approaches for improving mental health and facilitating posttraumatic growth in these patients.